Performance of Vasopressin Stimulated Bilateral Inferior Petrosal Sinus Sampling in Corticotropin Dependent Cushing’s Syndrome with Negative or Equivocal 3 Tesla Contrast Enhanced Magnetic Resonance Imaging of Pituitary - Puneet Shivnani; Rajeev Kasliwal; Gourav Goyal; Jyoti Sharma; Utkarsh Balani; Pankaj Gupta; Bhawani S. Sharma; Dinesh Yadav; Vineet Mishra; Surendra K. Sharma (Indian Journal of Endocrinology and Metabolism)
Introduction: Corticotropin releasing hormone (CRH)-stimulated bilateral inferior petrosal sinus sampling (BIPSS) is the most accurate procedure in the differential diagnosis of adrenocorticotropic hormone (ACTH)-dependent Cushing’s syndrome (CS) with a sensitivity of 88–100% and a specificity of 67–100%. However, CRH is not available globally currently. We undertook this study of BIPSS using lysine vasopressin (LVP) as an agent to stimulate the release of ACTH from corticotrophs. Our objective was to assess the accuracy of LVP-stimulated BIPSS in differentiating Cushing’s disease (CD) from ectopic ACTH syndrome (EAS) with negative or equivocal 3T contrast-enhanced MRI (CEMRI). Methods: Seventeen patients with clinically and biochemically confirmed ACTH-dependent CS with equivocal or negative CEMRI pituitary underwent BIPSS using LVP as a stimulating agent. Results: Of seventeen patients who underwent BIPSS, nine patients had a raised central-to-peripheral ACTH ratio and were classified as having CD that was confirmed on histopathology following transsphenoidal sinus surgery. Remaining eight patients, who did not show a raised central-to-peripheral ACTH ratio, were classified to have EAS. All patients with EAS underwent contrast-enhanced computerised tomography of the neck, chest, and abdomen and/or Gallium 68 DOTANOC positron emission tomography/computerised tomography. Seven out of eight patients demonstrated solitary pulmonary nodule in the lung (bronchial carcinoid), and one patient had a mass in the thymus (thymic carcinoid). Conclusion: BIPSS using LVP confirmed the source of ACTH excess correctly in all the patients with ACTH-dependent CS without the loss of specificity.